Pesticide Use and Health Complaints among Farmers in Lata Lanyir Village, Lewa Tidahu Sub District, East Sumba Regency - Noberthon Mberulata; Noorce C. Berek; Agus Setyobudi (Media Kesehatan Masyarakat, 2022)
Pesticide is a chemical substance used to prevent or kill pests. However, the use of pesticides that does not follow the instruction will cause health problems. This study aims to describe the pesticide use and health problems in farmers in Lata lanyir Village, Lewa Tidahu Sub District, East Sumba District. This type of research was descriptive. The population consisted of 150 farmers in Lata Lanyir Village. The sample in the study was 60 farmers selected by using a simple random technique. The data obtained in this study were analyzed descriptively and presented in tables and narratives. The results showed that the method of mixing pesticides was mostly by the instructions (76.67%), the method of spraying pesticides was according to the direction of the wind (73.33%). Also, farmers did not use PPE such as protective clothing (78.33%), gloves (73.33%), boots (85%), and masks (30%). Health complaints felt by farmers were headache (53.33%), itching (63.33%), nausea (40%), and fatigue (20%). Farmers need to pay more attention to the instructions for using pesticides listed on the label to reduce the risk of pesticide poisoning and to use personal protective equipment when working with pesticides.